Suppressive efficacies of antimicrobial agents against human peripheral-blood mononuclear cells stimulated with T cell mitogen and bacterial superantigen - Maeda, Masaki; Ishii, Hidetoshi; Tanaka, Sachiko; Onda, Kenji; Hirano, Toshihiko (Arzneimittelforschung, 2010)
The immunomodulatory efficacies of 12 antimicrobial agents clinically used were examined against T cell mitogen- or bacterial superantigen-induced proliferation of peripheral-blood mononuclear cells of healthy subjects. Minocycline (CAS 13614-98-7), rifampicin (CAS 13292-46-1), trimethoprim (CAS 738-70-5), and ribavirin (CAS 36791-04-5) significantly inhibited the proliferation of mitogen-stimulated mononuclear cells at 1 – 100 µg/ml (p < 0.001), whereas ofloxacin (CAS 82419-36-1) enhanced the proliferation (p < 0.001). Ampicillin (CAS 69-53-4), lincomycin (CAS 859-18-7), vancomycin (CAS 1404-93-9), sulfamethoxazole (CAS 723-46-6), fosfomycin (CAS 26016-99-9), Colistin (CAS 1264-72-8), and polymyxin B (CAS 1405-20-5) showed no significant effect. Minocycline, rifampicin, trimethoprim, and ribavirin also inhibited the proliferation of superantigen-stimulated peripheral-blood mononuclear cells at 1–100 µg/ml (< 0.001), whereas ofloxacin stimulated the proliferation (p < 0.001). Rifampicin and minocycline at 10–100 µg/ml significantly inhibited interleukin-2 production from mitogen-or superantigen-stimulated peripheral-blood mononuclear cells (p < 0.025). These results suggest that certain kinds of antimicrobial agents inhibited the proliferation of mitogen- and superantigen-stimulated human peripheral-blood mononuclear cells and suppressed interleukin-2 production from these cells. The ofloxacin effect is immunostimulative, while the drug did not influence the interleukin-2 production.
Keywords: Antimicrobial agents, immunomodulatory effect; Human peripheral lymphocytes; Interleukin-2; Toxic shock syndrome toxin 1